PENDIDIKAN KARAKTER SEBAGAI UPAYA MENJAGA KESEHATAN MENTAL BAGI MAHASISWA - Nurngain, Alfan; Imron, Ali (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
This research aims to investigate how the efforts of character education contribute to maintaining mental health. In addition to the implemented character education, this study delves into the impacts of character education in safeguarding the health of students. This research adopts a literature review methodology with a qualitative-descriptive approach. Data are collected from various sources such as books, journals, and other supporting documents. The analysis employed in this research is content analysis. The implementation of this research includes character education in the curriculum, social skills and empathy, leadership and responsibility, morality and life balance, development of support systems, community involvement in character education, enhancement of resilience, and stress management. The identified impacts encompass the formation of positive values, interpersonal skills, social support and empathy, and student.